Sokrat II - An International, Prospective, Multicenter, Phase IV Diagnostic Trial to Evaluate the Efficacy of the Wrist SAFE Algorithm in Fracture Sonography of Distal Forearm Fractures in Children - Ackermann, Ole; Wojciechowski, Piotr; Dzierzega, Maria; Grosser, Kay; Schmitz-Franken, Ansgar; Rudolf, Henrik; Eckert, Kolja (Ultraschall in der Medizin, 2019)
Distal forearm fractures are the most common fractures in childhood and can be diagnosed with ultrasound. The aim of this study was to demonstrate the eligibility of Wrist SAFE for clinical use and the avoidance of X-ray application in children. We enrolled patients from 0 - 12 years with suspected distal forearm fractures. They were treated according to the Wrist SAFE algorithm, a detailed pathway for ultrasound fracture diagnosis, treatment decisions and control options. Additionally, 9 clinical predictors were tested. Depending on sonographic and clinical findings, patients were treated with functional movement, immobilization or surgery. Follow-up was conducted after 5 days and 3 months. 16 physicians (6 specialists, 10 assistants) at 5 study sites examined 498 (234 boys, 251 girls, 13 not specified) patients with ultrasound, age 8.4 (0 - 12) years. 321 (64 %) patients were diagnosed with a fracture, 5 (0.8 %) with suspected fracture; X-rays were conducted in 58 cases (12 %), 9 (1.8 %) of them on day 1 and 49 (9.8 %) on day 5; sonographic diagnosis was confirmed in 57 of 58 (98 %) cases; in one case, the sonographic diagnosis of "contusion" was revised to "radius fracture". 381 patients (77 %) underwent final follow-up after an average of 96 (62 - 180) days. All patients were symptom-free at that time. Palpatory bone pain over the radius/ulna and swelling were identified as clinical predictors. 81 % of X-rays were avoided. Wrist SAFE enables the safe diagnosis and therapy of distal forearm fractures in children. Findings can be reviewed safely, also enabling physicians in training to use the method. 81 % of X-rays can be avoided, a figure that corresponds to 2.8 million X-rays in the G10 member states. After performing 100 examinations, physician have acquired the necessary sonography skills.